Time Management: Menggunakan Waktu Secara Efektif dan Efisien - Gea, Antonius Atosökhi (Bina Nusantara University, 2014)
Living in the midst of a changing business environment, which many people are burdened with more than one responsibilities, especially in a company with very high business activity and also in highly competitive industry, is imperative for the leaders of the company to be able to manage their time well in order to survive and be able to move in a sustainable manner. The concept of time management began during the industrial revolution and became a modern idea about doing things effectively and efficiently. Time management is one of the basic skills needed to be successful in life. The findings of various surveys indicated that time management enabled organizations or companies learn to survive in the face of competition and achieve a lot of success in business.